(untitled) (Journal of the College of Basic Education, 2022)
Existentialism perceives the other as an entity set to deprive the self of its freedom Thus, relations between men and women are affected by this view, as each sees that the other is trying to control and rob him of his freedom therefore we find that each of them tries to be the dominant side and not the weak one _and in the novels of inaam kachachi it can be noted that she has added this type of existential love to most of the relationships amongst her characters. This study dealt with love and its representations in the novels of Inaam Kachachi (Sawaqi Al Quloub), (American Granddaughter) , (Tushari), (al nabitha) and we discussed the contents of these narrations and tried to explore their ideas and the implications they contained of the existential ideas, and the study has adopted the descriptive analytical method as well as the interpretation of the reconciliation of texts and existential ideas to reveal the meanings of existential love and other types of love in novels and the study has reached the conclusions that female characters are more powerful and dominant opposed to the obvious weakness and negativity of male characters as well as the multiplicity of types of love in the novels ,such as existential love, sensual and instinctive love, and emotional love.